2002
DOI: 10.1007/s00415-002-0756-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical types of Wilson's disease and glucose metabolism in extrapyramidal motor brain regions

Abstract: In Wilson's disease a disturbed glucose metabolism especially in striatal and cerebellar areas has been reported. This is correlated with the severity of extrapyramidal motor symptoms (EPS). These findings are only based on a small number of patients. Up to now it is unknown whether EPS are caused by various patterns of disturbed basal ganglia glucose metabolism. We investigated 37 patients and 9 normal volunteers to characterize the disturbed glucose metabolism in Wilson's disease more precisely. The glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
2
17
0
10
Order By: Relevance
“…The data from this study demonstrated age-dependent changes of 64 Cu accumulation in the brains of Atp7b −/− knockout mice, which are encouraging and support further investigation of age-dependent changes of copper metabolism in WD patients who suffer from psychiatric and neurological symptoms, using [ 64 Cu]CuCl 2 -PET/CT imaging in conjunction with [ 18 F]FDG PET [34, 35] and MRI [35, 36]. Delineation of age-dependent changes of copper metabolism in WD patients is expected to contribute to a better understanding of molecular mechanism of neurodegeneration in WD.…”
Section: Discussionsupporting
confidence: 64%
“…The data from this study demonstrated age-dependent changes of 64 Cu accumulation in the brains of Atp7b −/− knockout mice, which are encouraging and support further investigation of age-dependent changes of copper metabolism in WD patients who suffer from psychiatric and neurological symptoms, using [ 64 Cu]CuCl 2 -PET/CT imaging in conjunction with [ 18 F]FDG PET [34, 35] and MRI [35, 36]. Delineation of age-dependent changes of copper metabolism in WD patients is expected to contribute to a better understanding of molecular mechanism of neurodegeneration in WD.…”
Section: Discussionsupporting
confidence: 64%
“…The severity of neurological deficits was assessed using an established semiquantitative scale: 0 (no deficits), 1 (only dysarthrophonia), 2 (mild deficits) , 3 (moderate deficits), 4 (severe deficits) and 5 (very severe deficits) [8].…”
Section: Methodsmentioning
confidence: 99%
“…For the latter case one can further differentiate between pseudo-sclerotic (PS) and pseudo-parkinsonian (PP) cases according to their fine-motoric disturbances caused by the neurological impairments [47]. Frequently, a merged type (MT) between them is considered, which can be seen neurologically belonging to PP [51].…”
Section: Exemplary Application -Classification Of Morbus Wilsonmentioning
confidence: 98%